Uniting disciplines against antimicrobial resistance (AMR): highlights from a multidisciplinary inaugural AMR summit - Brittany Rodriguez; Andrea M. Prinzi; Brandon K. Hill; Robert Tibbetts; Heinz Salazar; David McAdams; Awilda M. Rivera-Acosta; Minkey Wungwattana; Suzane Silbert; Denver T. Niles (Antimicrobial Stewardship & Healthcare Epidemiology)
Antimicrobial resistance (AMR) poses a significant global health threat, projected to cause 10 million deaths annually by 2050. Addressing AMR requires a coordinated, multidisciplinary approach encompassing infectious disease (ID) clinicians, pharmacists, microbiologists, infection preventionists, and policymakers. The inaugural AMR Summit, hosted by bioMérieux in collaboration with Tampa General Hospital and the University of South Florida Morsani College of Medicine in November 2024, convened experts from various fields to explore innovative strategies for combating AMR. Key topics discussed included the role of multidisciplinary teams in antimicrobial stewardship programs, advancements in rapid diagnostic tests and antimicrobial susceptibility testing, the application of implementation science in AMR, and the integration of next-generation sequencing in ID diagnostics. The summit underscored the importance of diagnostic innovation, interdisciplinary collaboration, policy, advocacy, and public engagement in advancing efforts against AMR.